Процедура ампаро як форма конституційного контролю в Мексиці - Шевчук, Ірина Миколаївна; Shevchuk, Iryna M. (Міжнародний гуманітарний університет, 2015)
У статті досліджено виникнення, становлення та розвиток інституту конституційного контролю в Мексиці. Охарактеризовано принципи й особливості процедури ампаро як спеціалізованого інституту конституційного контролю. Визначено, що процедура ампаро– ефективний засіб захисту Конституції, прав людини та громадянина й дієвий інститут конституційного контролю. Конституційний контроль у Мексиці здійснюється судами загальної юрисдикції.

The article analyzes the origin, formation and development of the constitutional control institute in Mexico. The main principles and features of amparo procedure, as a specialized constitutional control institute are characterized. It is determined that amparo procedure is an effective mean of protection of Constitution, the rights of human and citizen. Amparo procedure is viewed as effective institute of Constitutional control. Constitutional control in Mexico is realized by the courts of general jurisdiction. The following constitutional principles of amparo procedure are characterized: the principle of party initiative, principle of direct personal damage presence of the injured party that should be caused in the form, prescribed by the law; the principle of justice execution in the limits of amparo procedure, realized only by the court; principle of relativity of decisions, principle of finality of amparo procedure. The number of following features of amparo procedure, as a specialized institute of constitutional control are determined: a complaint about verification of the constitutionality of laws or other legal regulations can be submitted by any natural person or legal entity; the argument of the complaint should be the law violation that is guaranteed by the constitution; the purpose of the complaint is exemption of individual from application of this act to him/her; the check of normative act constitutionality is made through an open trial, the parties of which are the prosecutor and the responsible public authority that issued this normative act; the decision that is made by the authorized court concerning the check of constitutionality of impugned normative acts is necessary only for the parties that take part in this process.
Amparo procedure as a form of constitutional control in Mexico
Keywords: процедура ампаро; конституційний контроль; основні права і свободи людинита громадянина; американська модель конституційного контролю; європейська модель конституційного контролю; amparo procedure; constitutional control; fundamental rights and freedoms of man and citizen; American model of constitutional control; European model of constitutional control